Faktor-Faktor yang dapat Mempengaruhi Keinginan Nasabah untuk Menggunakan Product Bundling Ziswaf pada Bank Muamalat KCP Sukaramai - Mina Hasin; Mustapa Khamal Rokan (Universitas Jember, 2022)
In an effort to improve the welfare of the community, philanthropy is an effort that provides solutions to overcome the people who live within. Islam is often about the teachings of philanthropy. By taking a study of ZISWAF's Product Bundling. Therefore, this study aims to determine marketing strategies and factors that can influence customer interest or desire in using ZISWAF Product Bundling and the process of obtaining benefits from this product at Bank Muamalat Medan Sukaramai. The methodology of this research is descriptive qualitative with an empirical approach, because the purpose of this research is to describe a situation that is factual in a systematic and accurate manner. The results showed that what made customers interested in using ZISWAF Product Bundling were Product Innovation Factors, Marketing Strategy Factors, Trust Factors, Product Quality Factors, and Income Factors. Then, that the ZISWAF Product Bundling referred to in this study is the discovery of banking products from Bank Muamalat which can be a financial investment as well as an investment in the afterlife. Product innovation is in the form of Savings and Deposits which are bundled with the ZISWAF program. Keywords: Product Bundling ZISWAF, Marketing Strategy, Islamic Bank